2008
DOI: 10.1007/s00455-008-9169-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aging on Hypoglossal Motoneurons in Rats

Abstract: Aging can result in a loss of neuronal cell bodies and a decrease in neuronal size in some regions of the brain and spinal cord. Motoneuron loss in the spinal cord is thought to contribute to the progressive decline in muscle mass and strength that occurs with age (sarcopenia). Swallowing disorders represent a large clinical problem in elderly persons; however, age-related alterations in cranial motoneurons that innervate muscles involved in swallowing have been understudied. We aimed to determine if age-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…These numbers coincided well with the corresponding data available in the literature characterizing hypoglossal motor neurons (range: 11-34 lm; mean 6 s.e.m. : 22.7 6 0.68 lm) (Schwarz et al, 2009). Similar histograms have been constructed from the stained profiles visible in the oculomotor nuclei of both strains (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These numbers coincided well with the corresponding data available in the literature characterizing hypoglossal motor neurons (range: 11-34 lm; mean 6 s.e.m. : 22.7 6 0.68 lm) (Schwarz et al, 2009). Similar histograms have been constructed from the stained profiles visible in the oculomotor nuclei of both strains (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The size distribution of the PV-positive cellular profiles was determined by using the appropriate built-in function of the IPP program, and then frequency histograms were constructed in each group that were compared with those of motor neurons in the corresponding nuclei available in the literature (Eberhorn et al, 2006;Schwarz et al, 2009). …”
Section: Light Microscopic Evaluation Of Parvalbumin Immunostainingmentioning
confidence: 99%
“…In rodents eccentric training promotes hypertrophy and growth-related signaling (Ochi et al, 2011; Tsumiyama, et al, 2014; Heinermeier et al, 2007). Finally, hypoglossal motoneuron number is preserved with age in mouse, rat and human (Gai et al, 1992; Sturrock, 1991; Schwarz et al, 2009), protecting tongue muscles from motoneuron-loss-induced denervation/reinnervation remodeling that typifies some appendicular muscles and is thought to promote type II-to-I conversion, MHC hybridization and fiber atrophy (Drey et al, 2014). Hypoglossal motoneurons also receive inputs from numerous central and peripheral sources, and it is possible that this rich synaptic milieu supports hypoglossal motoneurons during dysfunction in any one projection system.…”
Section: 4 Discussionmentioning
confidence: 99%
“…Age-related changes in GG muscle structure and physiology have been noted in humans and in animal models (11,15,28,45,50,56,67,68,71,75). Exercise may serve as an effective remediation because recent studies have identified increased GG muscle contraction amplitudes with exercise, as measured with electromyography (EMG) (73,83,88).…”
mentioning
confidence: 99%